GLOBALIZATION EDUCATION IN UZBEKISTAN: REFORMING THE EDUCATION SYSTEM IN UZBEKISTAN WITH THE PARTNERSHIP OF INTERNATIONAL ORGANIZATION - Zaylobidinova Munira (Journals Park Publishing, 2022)
This article explores the historical development of the education in Uzbekistan during Soviet Union period till our days. Additionally, it discusses the challenges on promoting the education in the country after the collapse of Soviet Union. Also it states the significant role of international organizations in reforming Uzbek model in education.
Keywords: International organization, Globalization, education system of Uzbekistan, Soviet Union